آجال الدفع بين المهنيين - يحي, أمين (جامعة الوادي University of Eloued, 2019)
الملخص: من المتعارف عليه ، أن يوافق الممون على منح آجال الدفع لعملائه تحت عملية القرض التمويلي أو من خلال قرض فيما بين المؤسسات . إلا أن هذه الممارسة تؤثر على الاقتصاد والمؤسسات التي تلعب دور بنك ، كما تشكو العديد من مؤسسات تموين من الإفراط في التمديد المتتابع لآجال الدفع التي تفرضها مؤسسات التوزيع الكبرى، بالإضافة الى انه يصعب الحد من حرية التفاوض بين الأطراف في العلاقات التجارية ولا توجد أحكام عامة تحدد بطريقة ردعية الأجل الأقصى للدفع، بل مجرد أحكام تتعلق ببعض المنتوجات. لذلك تدخل المشرع من اجل تخفيض آجال الدفع وحظر حصول العون على آجال دفع تعسفية، غيران المسار التحفيزي من قبل المشرع بالنص على عقوبات باء بالفشل ، لذلك يجب الأخذ بعين الاعتبار على نطاق واسع عادات المهنيين. Summary: It is habitual for suppliers to grant payment terms to their buyer. This practice is referred to as supplier credit or business-to-business credit. However, it is not good for the economy and for companies that they play the role of banker. Indeed, many suppliers complain about the excessive length of payment delays imposed on them by retail companies. Their efforts did not really succeed. Because it has proved difficult to limit the parties autonomy to negotiate in commercial relations. There is no general rule in law defining the maximum duration of payment periods as a matter of law. There is some arrangement concerning about specified products. As a result, the legislator goings-on to reduce the time required for payment and it is forbidden, to an economic agent to obtain improper payment terms. The legislator has provided for sanctions but the reason has failed. However, professional usage is largely taken in consideration.
Keywords: الأجل ; المهنيين ; التعسف ; التاخير ; الدفع ; المسؤولية ; غرامة